Signs of the Displacement of Guaymi in Sociolinguistic Stories - Marín Esquivel, Rebeca (2019)
Based on the individual sociolinguistic stories (also known as "life history" or "linguistic biography") of six bilingual speakers of Spanish and Guaymí, signs of the evident displacement of Guaymí in favor of Spanish are shown. This was achieved with a semi-structured interview that guided the conversation between the interviewees and the researcher. As a result, it was possible to confirm sociolinguistic differences related to age, schooling and the use of one language or the other according to the communicative context.